Challenges and Solutions in Teaching English at the Elementary School Level: A Case Study at SDN Pabelan 03 - Bayumegawira Kusuma Wardana; Muamaroh Muamaroh (English Teaching and Linguistics Journal (ETLiJ), 2026)
This study aimed to explore the challenges faced by the English teacher in the learning process and solutions to address these challenges at SDN Pabelan 03, Sukoharjo Regency, Central Java. A qualitative case study method was used to gain a deeper understanding of the teacher’s classroom teaching experiences across several grade levels. Classroom observation was conducted at the 1st, 3rd, and 6th grades,while semi structured interview was carried out by the writer to the English teacher as research participant. The data were analyzed using qualitative methods, including data reduction, data display, and conclusion drawing.The three main challenges faced are differences in students’ language abilities, variation in students' learning motivation, and limited supporting learning facilities. In response, the teacher implemented three strategies to address the issue: adapting material to the students' abilities through simple explanations and using translation to Indonesian, increasing student learning motivation through reward and educative consequences, and utilizing available resources such as internet facility and digital tools (Canva, and ChatGPT) to create supplementary teaching materials.